Inflammation and macrophage polarization in cutaneous melanoma: Histopathological and immunohistochemical study. (December 2016) - Scali, Elisabetta; Mignogna, Chiara; Di Vito, Anna; Presta, Ivan; Camastra, Caterina; Donato, Giuseppe; Bottoni, Ugo
Tumor-associated macrophages (TAMs) are considered to affect tumor growth and progression. Macrophages can be classified into two states of polarized activation, namely classically activated M1 macrophages and alternatively activated M2 macrophages. The dynamic balance between TAMs and tumor cells has an important impact on tumor homeostasis and progression. The aim of this study was to characterize the phenotype of TAMs present in different subtypes of superficial spreading cutaneous melanoma and their relationship with the lymphocytic infiltrate in order to identify new histopathological tools for melanoma prognosis and suitable targets for melanoma therapy. We selected four groups of patients with malignant melanoma in order to analyze the profile of polarized macrophage activation using immunohistochemical methods. Histopathological analysis showed that the macrophage polarization state appears to be more related to the lymphocytic infiltrate than to the thickness of the lesions. Further studies are necessary to increase understanding of the immunopathological dynamic of melanoma that may be modulated by future targeted immunotherapies.